Young women’s perceptions towards the Hijab Try-on app - Zulkifli, Abdul Nasir; Mohd Pozi, Nur Syuhada; Ismail, Salina (Science and Engineering Research Support Society, 2020)
Conventional hijab shopping requiresthe shoppers to go to the physical store to select and try the hijab themselves. This formof shopping needs theshoppers to allocate theirtime and effort. Meanwhile, online shopping has made it easier to shop where shoppers can get the goods they need without having to go to the store and this saves them a lot of time and effort. However, when it comes to online shopping for hijab, shoppers can only base their hijab purchase on the sizing chart and 2D photos. They are not accurate and interactive enough to allow shoppers to make the right choice. As such, for this kind of situation, a new approach to shopping and at the same time be able totry on the favourite hijabs is required. In this paper, weintroduce the Hijab Try-Onapp, a mobile augmented reality application which allows women shoppers to freely browse, select and try-on their favourite hijab at their own convenience using their own smartphone. The users can try-on the hijabs on their own or with the help of their friends or husband anytime and anywhere. The aimof this appis to enable the app’s users to try-on the hijabs provided by the app without having to try them in the fitting room.This feature can further enhance the existing capabilities which are lacking in online shopping.The purpose of this study is to investigate the potential of using the Hijab Try-On appamong a sample of 120 female young adults between the ages of 18 to 35years old.The study specifically focusing on enjoyment, perceived augmentation, perceived usefulness, perceived ease of use, attitude toward use and intention to use. The findings of the study showed that the participantsstrongly agreed on all the attributes namely; perceived ease of use, perceived usefulness, attitudetowards use, intention to use, enjoyment, and perceived augmentation. The mean value for intention to useis 4.46 which is thehighest while the mean valuefor perceived usefulness is4.14 which is the lowest.As a recommendation, owners of online hijab stores should be aware of the technological advances associated with virtual try-on. They need to incorporate and utilise the technology to provide convenience and comfort to their customers.